Depiction of Systemic Racism in Hidden Figures Movie by Theodore Melfi - Rahmalia, Ana (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
Racism is an act of differentiating behavior towards a society that is considered inferior by those who feel as superior. Racism is also divided into several dimensions, one of which is systemic racism which is closely related to regulations that affect people's lives in main sectors such as public facilities which include libraries and courts, and education. The purpose of this study is to describe the depiction of acts of racism in Hidden Figures Movie by Theodore Melfi. The research method used is a qualitative-descriptive research method, which focuses on research results in the form of descriptions. The data collection techniques used were listening and note techniques, as well as data analysis techniques used including data condensation, data display, and conclusions and verification. The results of this study state that the systemic racism contained in the film Hidden Figures applies to public facilities such as public library, court, as well as workplaces and schools. Keywords: Hidden Figures, Racism, Systemic Racism